Memahami Kepuasan Pelanggan terhadap Pelayanan Hotel: Suatu Tinjauan Pustaka Sistematis - Rina Suprina; Heny Hendrayati; Vanessa Gaffar; Ratih Hurriyati (IPB University, 2022)
Customer satisfaction is an important factor in the management of the hospitality industry because satisfied customers tend to revisit and provide recommendations to others so that in the end it will provide benefits for the hotel. This paper aims to review the literature related to hotel guest satisfaction. To obtain literature data, the Publish or Perish software was used and the Google Scholar and Scopus databases in Publish or Publish were selected. The title word used is